Influence of refined hierarchical martensitic microstructures on yield strength and impact toughness of ultra-high strength stainless steel. (15th August 2020) - Luo, Haiwen; Wang, Xiaohui; Liu, Zhenbao; Yang, Zhiyong
Abstract: The hierarchical martensitic features in ultra-high strength stainless steel (UHSSS), including the prior austenite grains, martensite packets, blocks and laths with the descending size, were refined to various extents by employing different thermomechanical processes and then carefully characterized. Their relation to yield strength and impact toughness was analyzed. We conclude that the refinement of martensitic structures could lead to the significant increase of yield strength, which follows the Hall-Petch relation with the effect grain size defined by high angle boundaries (HABs). Impact toughness of UHSSS depends on the frequency and capability for retained austenite (RA) grains at both HABs and martensite lath boundaries to trap the propagating cracks via strain-induced transformation, in which the film-like RA grains at lath boundaries appear to make the greater contribution.